Investigation on the Implementation of Exponential Rate Reaching Law on Parabolic Dish Antenna System - Nantim, James; Mohammed, A.; Sadiq, A. A.; Nazif, D. M. (Darul Yasin Al Sys, 2025)
Parabolic antennas are crucial in applications like satellite communication, radar systems, and radio astronomy for precise pointing and tracking capabilities. The research aims to create a reliable Exponential Rate Reaching Law-based Proportional-Integral-Derivative (ERPID) controller for a Parabolic Dish Antenna System, overcoming challenges like nonlinearities and wind disturbances. The study integrates the parabolic dish antenna model with PID and ERPID control, evaluating their performances under wind disturbances through simulations. In undisturbed conditions, the antenna system without a controller shows a slow rise time (7.5717 seconds) and extended settling time (9.8105 seconds). When a disturbance is introduced, the system becomes highly unstable with a rapid rise time (0.1047 seconds) and extreme overshoot (657%), demonstrating the need for a controller to manage disturbances​. When PID was introduced without Disturbance, the PID controller significantly improved the response. The rise time decreases to 1.4896 seconds, with a settling time of 5.2740 seconds. An overshoot of 9.63% indicates a controlled and responsive system. With Disturbance, the system maintains stability with a rise time of 1.4977 seconds, though the settling time increases slightly to 9.6556 seconds. Overshoot is kept minimal at 7.9%, showcasing the PID controller's ability to handle disturbances effectively​. Without Disturbance, the ERPID controller demonstrates a slower rise time (2.8663 seconds) than the PID, with a comparable settling time of 5.2298 seconds. Overshoot is minimized to 7.66%, indicating high stability and controlled precision. With Disturbance, the ERPID controller maintains a gradual response with a rise time of 2.9832 seconds and a settling time of 6.4649 seconds. The overshoot is further reduced to 6.04%, reflecting robustness against external factors and controlled performance under disturbance. The research revealed that the ERPID controller, despite improving system performance, is more effective for high-precision applications like satellite communication due to its enhanced stability and reduced overshoot.